Mucormycosis - Can the diagnosis be challenging at times?? - Vandana Raghunath; K Hanna Rose Priyanka; C Geetha Kiran; R Manasa Deepthi (Wolters Kluwer Medknow Publications, 2018)
Mucormycosis is an aggressive and often rapidly progressing fatal form of fungal infection mainly affecting the immunocompromised patients and characterized by destruction and necrosis. The paranasal sinuses get affected commonly in the rhinocerebral type with or without oral cavity involvement. At times, even in the setting of immunosuppression, it presents as a subtle clinical infection posing both as a diagnostic and therapeutic challenge to the clinicians. Further, in such immunocompromised cases, early diagnosis and prompt treatment become utmost demanding to prevent the ensuing morbidity and mortality. We present one such indolent case which presented as a sinus infection in a 50-year-old diabetic woman. Further, the granulomatous presentation on hematoxylin and eosin-stained sections led to an erroneous initial diagnosis, which later upon Grocott's methenamine silver staining was diagnosed as mucormycosis-rhinocerebral type. Thus, both clinical and histopathological presentations were defying.